Genome-wide association study for grain zinc concentration in bread wheat (Triticum aestivum L.) - Ma, Jianhui; Ye, Miaomiao; Liu, Qianqian; Yuan, Meng; Zhang, Daijing; Li, Chunxi; Zeng, Qingdong; Wu, Jianhui; Han, Dejun; Jiang, Lina (Frontiers in Plant Science, 2023)
Zinc (Zn) deficiency causes serious diseases in people who rely on cereals as their main food source. However, the grain zinc concentration (GZnC) in wheat is low. Biofortification is a sustainable strategy for reducing human Zn deficiency. In this study, we constructed a population of 382 wheat accessions and determined their GZnC in three field environments. We found that GZnC of the wheat accessions showed an increasing trend with their released years, indicating that the dominant allele of GZnC was not lost during the breeding process in China. Phenotype data was used for a genome-wide association study (GWAS) using a 660K single nucleotide polymorphism (SNP) array, and nine stable quantitative trait loci (QTLs) for GZnC were identified on chromosomes 3A, 4A, 5B, 6D, and 7A. Haplotype analysis identified an important candidate gene for GZnC, namely, TraesCS6D01G234600, and GZnC between the haplotypes of this gene showed, significant difference (P ≤ 0.05) in three environments. This study provides new insights into valuable markers and candidate genes for wheat biofortification to improve GZnC.